2005
DOI: 10.2174/1568010053586309
|View full text |Cite
|
Sign up to set email alerts
|

The Role of β2-Adrenergic Receptors in Inflammation and Allergy

Abstract: Essential role of beta(2)-adrenoreceptor (beta(2)AR) in airway relaxation is well established. Nevertheless, beta(2)AR seems playing an actual role in allergy and inflammation. Interaction between beta(2)AR and proinflamatory cytokines in airway smooth muscle has been revealed. Being located on proinflamatory cells, beta(2)ARs may influence function of these cells in vivo. It was clear established, that stimulation of beta(2)AR inhibits release of proinflamatory mediators from mast cells, influences T-cell gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 90 publications
2
19
1
1
Order By: Relevance
“…The results described here provide a mechanism by which the expression of TTP can be turned off at sites of inflammation. ␤ 2 -Agonists have been reported to have antiinflammatory effects in various in vitro conditions but these actions do not clearly translate into the in vivo situation, e.g., in inflamed lung tissue in patients with asthma (Sitkauskiene and Sakalauskas, 2005). The mechanism described in the present study and in our earlier study (Jalonen et al, 2007) could, at least partly, explain the discrepancy between these in vitro and in vivo findings.…”
Section: Discussioncontrasting
confidence: 76%
“…The results described here provide a mechanism by which the expression of TTP can be turned off at sites of inflammation. ␤ 2 -Agonists have been reported to have antiinflammatory effects in various in vitro conditions but these actions do not clearly translate into the in vivo situation, e.g., in inflamed lung tissue in patients with asthma (Sitkauskiene and Sakalauskas, 2005). The mechanism described in the present study and in our earlier study (Jalonen et al, 2007) could, at least partly, explain the discrepancy between these in vitro and in vivo findings.…”
Section: Discussioncontrasting
confidence: 76%
“…In addition to bronchodilatation, salbutamol and other β 2 -agonists have been shown to have some anti-inflammatory effects (Bissonnette and Befus, 1997;Broadley, 2006;Johnson, 2002;Sitkauskiene and Sakalauskas, 2005). Inflammatory cells including macrophages express β 2 -adrenoceptors on their cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of β 2 -adrenoceptors leads to a series of events that induce airway smooth muscle relaxation and also to some antiinflammatory effects (Bissonnette and Befus, 1997;Broadley, 2006;Giembycz and Newton, 2006;Johnson, 2002Johnson, , 2006Sitkauskiene and Sakalauskas, 2005). β 2 -adrenoceptors activate adenylate cyclase that results in increased intracellular cAMP levels and activation of protein kinase A (PKA), which in turn regulates phosphorylation (activation) of target molecules and gene expression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ADRB2 stimulation could induce IgE production by human B lymphocytes and expression of the soluble low-affinity IgE receptor sCD23. 36,37 Obesity and ADRB2 Polymorphisms While it has been estimated that genetics explains 40% of population variability in the prevalence of obesity, conflicting results exist for the association of the ADRB2 Arg16 polymorphism and obesity. Several studies reported that increased BMI was associated with the Arg16 isoform, while other studies have revealed the opposite results.…”
mentioning
confidence: 99%